2019
DOI: 10.22391/fppc.503683
|View full text |Cite
|
Sign up to set email alerts
|

Memede kitle şikayeti olan hastalarda depresyon ve anksiyetenin değerlendirilmesi: prospektif bir çalışma

Abstract: Introduction: Breast cancer is the most common cancer among women in the world and in our country. Despite early diagnosis and improved treatment possibilities, breast cancer is difficult to accept and a major source of anxiety. It brings various psychosocial problems to the agenda. In this study, we aimed to evaluate the effect of depression and anxiety in the patients admitted to the outpatient clinic with the complaint of a mass in the breast and to determine the effect of mass on the mental health of women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Biracyaza et al reported a BDI score of 16.3 [ 26 ]. Mercan et al suggested a cut-off score of 17 for diagnosing depression among cancer patients [ 27 ]. According to Wedding et al, most BDI score alterations in cancer patients are related to somatic and not to affective symptoms and may be attributed not to depression but to the severity of the disease [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biracyaza et al reported a BDI score of 16.3 [ 26 ]. Mercan et al suggested a cut-off score of 17 for diagnosing depression among cancer patients [ 27 ]. According to Wedding et al, most BDI score alterations in cancer patients are related to somatic and not to affective symptoms and may be attributed not to depression but to the severity of the disease [ 28 ].…”
Section: Discussionmentioning
confidence: 99%